Pengaruh Pengelolaan Modal Kerja dan Struktur Modal Terhadap Profitabilitas Perusahaan pada PT. PLN (Persero) Sektor Pembangkitan Tarahan - Nur Syamsiyah; Tejo Waskito (Universitas Mitra Indonesia, 2020)
This research aims to know the manajemen of working capital and capital structure that consists of a variable cash turnover, inventory turnover, current ratio and debt to equity ratio to profitability. The population in this research is PT. PLN (persero) generation tarahan sector period of 2009-2013 of years. The result of this research showed that cash turnover, inventory turnover, current ratio and debt to equity ratio influential but not significantly to profitability.